Optimization of CNC Milling Parameters Machining on Surface Roughness and Hardness Value of Material SS 316 - Muhammad Wildan Syifatillah; Talifatim Machfuroh (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
CNC milling of stainless steel (SS) 316 faces considerable difficulties in obtaining the desired hardness and surface quality as a result of machining variability. This investigation focuses on the optimization of spindle speed, feed rate, and depth of cut using the Taguchi method, where soluble oil served as the cutting fluid. The Taguchi method was used with an L9 orthogonal array was implemented to design the experimental trials and the responses of surface roughness (Ra) and hardness (HRB) were quantified according to ISOstandards. The findings reveal that the minimum surface roughness is obtained at a spindle speed of 2100 rpm, feed rate of 50 mm/min, and depth of cut of 0.2 mm and the maximum hardness is achieved at 1500 rpm, 50mm/min, and 0.2 mm. Generally, higher feed rates and depths of cut contribute to poorer surface finish, whereas elevated spindle speeds are associated with improved surface quality. The observed reduction in hardness is primarily linked to thermal accumulation in the cutting zone, which is partlyalleviated by the use of soluble oil. These findings emphasize the need to consider distinct optimal conditions for surface roughness and hardness must be considered to ensure superior CNC milling outcomes for SS 316 stainless steel.